A formação profissional: trajetórias e expectativas dos estudantes nos cursos técnicos subsequentes - Moraz, Caterine Pereira (2015)
The study aimed to analyze, through the perception of entering and graduating students, the motivations and reasons that justify or explain their choices for subsequent mid-level technical professional education courses, seeking to understand the role of vocational education in their lives. Through the identification of students’ profile, which is manifested by their academic experiences and professional experiences, the study contextualized their family and school life and their life projects in view of the demands of the working world and the need for updating and continuing education. The research is theoretically based on the relationship between school, education, work and their impact in the working class, as well as on changes in the working world, it took as reference authors as Antunes, Ciavatta, Cunha, Enguita, Frigotto, Ferretti, Friedmann, Naville, Kuenzer, Ramos, Hirata and Saviani. The field research was developed through a qualitative survey, entering and graduating students from middle-level technical courses in Management and Events of Instituto Federal de Educação, Ciência e Tecnologia in Paraná, Curitiba campus, had participated answering questionnaires and giving interviews. The results were guided by the establishment of categories that favored the understanding of the reality experienced by the participants throughout their academic and professional careers, motivations and expectations of the educational and professional future mainly of students who theoretically could have applied for a job in graduate courses but opted for this type of education.